2022
DOI: 10.3390/toxins14050290
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1 Occurrence in Children under the Age of Five’s Food Products and Aflatoxin M1 Exposure Assessment and Risk Characterization of Arab Infants through Consumption of Infant Powdered Formula: A Lebanese Experience

Abstract: Aflatoxin M1 (AFM1) is a salient metabolite that can be used to assess Aflatoxin B1 (AFB1) exposure in humans and animals. The carcinogenic potency of AFB1 and AFM1 was severely reported. The aims of this study were (1) to survey the contamination level of AFM1 in the most traded infant powdered formula brands (IPF) (n = 42) along with the AFB1 level in under 5’s children food brands (biscuits, cornflakes, and cereals) (n = 42) and (2) to assess the estimated daily intake (EDI), the hazard quotient (HQ) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…In humans, AFs intoxication cause immunosuppression, mutagenicity, teratogenicity, and impaired child growth. In production animals, these toxins may cause weight gain and inadequate food conversion, besides liver disorders (Daou et al, 2022;Mostrom and Jacobsen, 2020). Aflatoxin M 1 (AFM 1 ) is the biotransformed form of AFB 1 excreted in milk and body fluids of animals.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, AFs intoxication cause immunosuppression, mutagenicity, teratogenicity, and impaired child growth. In production animals, these toxins may cause weight gain and inadequate food conversion, besides liver disorders (Daou et al, 2022;Mostrom and Jacobsen, 2020). Aflatoxin M 1 (AFM 1 ) is the biotransformed form of AFB 1 excreted in milk and body fluids of animals.…”
Section: Discussionmentioning
confidence: 99%
“…AFB 1 was detected in only one study by Reed and Moore (2009), who reported this mycotoxin in 15% of the pasture samples from Australia at levels of 14-15 µg/kg, which is close to the limit determined by the United States and EU for animal feed (European Commission, 2010;FDA, 2016). The occurrence of high levels of AFB 1 in feed of dairy cows is alarming, considering that 0.35-6.2% of the parent compound may be excreted into milk as AFM 1 (Souza et al, 2021), and the fact that this metabolite also exhibits carcinogenic properties and toxic effects on the liver, kidneys, hematopoietic stem cells, and immune system (Daou et al, 2022;Jafari et al, 2021;Mokhtarian et al, 2020). In addition, AFM 1 remains stable in milk and other dairy products even after conventional thermal processing performed in dairy plants (Pires et al, 2022;Souza et al, 2021), thus representing a remarkable danger to human health, especially to infants (0-12 months) (Daou et al., 2022;Jafari et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of high levels of AFB 1 in feed of dairy cows is alarming, considering that 0.35-6.2% of the parent compound may be excreted into milk as AFM 1 (Souza et al, 2021), and the fact that this metabolite also exhibits carcinogenic properties and toxic effects on the liver, kidneys, hematopoietic stem cells, and immune system (Daou et al, 2022;Jafari et al, 2021;Mokhtarian et al, 2020). In addition, AFM 1 remains stable in milk and other dairy products even after conventional thermal processing performed in dairy plants (Pires et al, 2022;Souza et al, 2021), thus representing a remarkable danger to human health, especially to infants (0-12 months) (Daou et al., 2022;Jafari et al, 2021). Hence, the absence of data from African and Asian continents, and the few data reported in South American countries stress the need for studies on the occurrence of mycotoxins in pastures from those regions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review by [1] estimated that 60% -80% of the world's food crops were contaminated by aflatoxin. Aflatoxin can harm human health, leading to death [2][3], cancer [4][5], immune system disruption [6], and stunted child growth [7][8]. Aspergillus flavus produces aflatoxin, a secondary metabolite that thrives in uncontrolled processing and storage condition [9].…”
Section: Introductionmentioning
confidence: 99%